2007
DOI: 10.1002/cmdc.200700104
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships for a Family of Benzothiophene Selective Estrogen Receptor Modulators Including Raloxifene and Arzoxifene

Abstract: The search for the "ideal" selective estrogen receptor modulator (SERM) as a substitute for hormone replacement therapy (HRT) or use in cancer chemoprevention has focused on optimization of estrogen receptor (ER) ligand binding. Based on the clinical and preclinical benzothiophene SERMs, raloxifene and arzoxifene, a family of SERMs has been developed to modulate activity and oxidative lability. Antiestrogenic potency measured in human endometrial and breast cancer cells, and ER ligand binding data were correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…5A). The SERM DMA, a ligand for both ER␣ and ER␤ (44,45), produced no significant effect in the presence of NOS or PI3K inhibition (Fig. 5B).…”
Section: Effects Of Estrogens and Antiestrogens In Presence Of Nos Blmentioning
confidence: 84%
“…5A). The SERM DMA, a ligand for both ER␣ and ER␤ (44,45), produced no significant effect in the presence of NOS or PI3K inhibition (Fig. 5B).…”
Section: Effects Of Estrogens and Antiestrogens In Presence Of Nos Blmentioning
confidence: 84%
“…7), developed by Eli Lilly and Company, is structurally related to raloxifene; however, early studies revealed improved in vivo potency and efficacy (Palkowitz et al, 1997;Sato et al, 1998a). In addition, whereas raloxifene shows more specificity for ERa versus ERb (21 versus 560 nM), arzoxifene displays properties of a dual ERa/ERb SERM (22 versus 66 nM) (Overk et al, 2007). Arzoxifene binds directly to the ER and prevents increased body weight and cholesterol levels in ovariectomized rats with similar efficacy as estrogen and raloxifene but with more potency than raloxifene Nuclear Receptors and Their Selective Modulators in reducing these parameters (Sato et al, 1998a;Suh et al, 2001).…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%
“…We have shown that derivatives and analogues of DMA can be synthesized that retain antagonist activity [42], [43], [44], [45], [46]. DMA derivatives and analogues with ER antagonist activity in breast and endometrium would be predicted to reduce the incidence of breast cancer in the clinic, as is observed with raloxifene.…”
Section: Resultsmentioning
confidence: 96%